Engineering education on sustainability and the reuse of electronic components: a novel, hands-on educational method that emphasizes student creativity - Nikoloudakis, Nikolaos; Rangoussi, Maria; Liarakou, Georgia; Sinioros, Panagiotis (Frontiers in Education, 2025)
IntroductionEngineering students are experientially introduced to the concepts of sustainability, recycling and the cyclic economy through a novel educational method proposed, implemented and evaluated within an Electrical and Electronics Engineering undergraduate curriculum.MethodsStudents work in groups in a hands-on laboratory to disassemble damaged electrical/electronic devices, reclaim electronic components, recycle the damaged ones and reuse the functional ones, either to repair similar devices or to design and construct new devices. Students get a lived experience of a collaborative sustainability project that aims at developing their cognitive, social/emotional and metacognitive skills, creativity being a central one among them. An educational intervention of two phases is implemented and evaluated via multiple tools.ResultsResults document student gains of varying degrees across all three domains of learning; an increase in creativity, in particular, is measured between the two phases.DiscussionThe formation of a community of learning is another important outcome that opens directions for future research.